Introduction: Queer Ruralisms - Poole, Ralph J.; Robbins, Ben (AmLit)
This special issue considers queer attachments to rural space in literature, which have often been obscured by privileging the urban in cultural depictions of queer lives. Queer studies scholarship has worked to overcome this urban bias to reveal the diversity of queer lives within rural environments. We make a new contribution to this research by exploring literary manifestations of queer ruralism in terms of narrative form and within the contexts of transmedial and transnational exchange. To illustrate these approaches, we introduce a range of recent works from the 2020s, with deep roots in American literary culture, that have contributed to the dissemination of queer rural texts. They have achieved this, first, by reframing characters' experiences within transnational contexts and, second, by engaging in cultural cross-pollination across diverse media. Here we focus on Genevieve Hudson's novel Boys of Alabama (2020), contemporary queer country music and music videos by Dixon Dallas, Willy Strokem, Tyler Childers, and Silas House, as well as literary precursors to these works in the fiction of JT LeRoy (Laura Albert) and Dorothy Allison. Across the work of these artists, negotiations across borders and media are used to explode the stereotypes and limiting roles associated with queer rural lives and to reinvent genres, such as the Southern Gothic or country music, in ways that centre non-normative sexual identities.